Exterior characteristics of female Gembrong goat in Karangasem, Bali - Atmoko, Bayu Andri (Fakultas Peternakan Universitas Brawijaya, 2017)
Gembrong goat is one of local genetic resources of livestock in Bali Province. The population is categorized as endangered and critical breed based of World Watch List for Domestic Animal in 1997. Currently its population under 50 individuals were spread in Bali Province. This paper explain the exterior characteristics of female Gembrong Goat was found in Karangasem Regency, Bali Province. Twelve female Gembrong Goat were observed including face appearance, coat colour, horn, ear appearance. Head and body measurements were obtained, including head length, head girth, ear length, chest girth, body length, withers height, hip height. The descriptive statistical analysis was applied due to the small size numbers of goat in this research. Female Gembrong goat have flat face appearance, small pointed horn, hanging to the side ear, and have white, brown, black coat colour dominant is 50%, 25% and 25% respectively. Result of the head measurement show that the average of head length, head girth, ear length, is 18,20±1,14 cm, 11,30±0,82 cm, and 14,20±2,04 cm respectively, so the head index is 62,08±0,72. Body size of female Gembrong Goat such as chest girth, body length, withers height, hip height respectively was 67,42±3,21 cm, 48,50±4,40 cm, 51,50±3,21 cm and 54,58±3,55 cm. In case compared with the Exterior characteristics of female Gembrong goat in previous research in 2004 and 2014, appears to decrease ear length and all of the body size, this indicates a decrease in genetic quality of Gembrong Goat was raised with traditional management by small farmer in Karangasem, Bali. Keywords: Gembrong